Dalit: Past, Present and future - Teltumbde, Anand (London Routledge, 2020)
This book is a comprehensive introduction to Dalits in India from their origin to the present day. Despite a plethora of provisions for affirmative action in the Indian Constitution, Dalits still suffer exclusion on various counts. The book traces the multifarious changes that befell them through history, germination of Dalit consciousness during the colonial period and its f lowering under the legendary leadership of Babasaheb Ambedkar. It provides critical insights to their degeneration during the post-Ambedkar period, taking stock of all significant developments therein such as the rise of the Bahujan Samaj Party, Dalit capitalism, NGOization of the Dalit discourse and the various implicit or explicit emancipation schemas thrown up by them.